Fluoride Risk Assessment from Consumption of Different Foods Commercialized in a European Region - Juan R. Jaudenes; Ángel J. Gutiérrez; Soraya Paz; Carmen Rubio; Arturo Hardisson (Applied Sciences, 2020)
Fluoride is a halogen found in soil and water from natural and anthropogenic sources. Foods, such as cereals, fruits, and vegetables, among others, absorb and accumulate fluoride. High intakes of this element produce toxic effects such as dental or skeletal fluorosis. Fluoride content was determined in a total of 144 samples from different food groups (cereals and derivatives, fruits, tree nuts, dry fruits, mushrooms, vegetables, and legumes) using selective fluoride ion potentiometry. The fluoride concentration stood out in almonds (3.70 ± 0.96 mg/kg), walnuts (3.53 ± 0.62 mg/kg), bread (2.54 ± 0.85 mg/kg), and rice (2.28 ± 0.93 mg/kg). Consumption of 236 g/day of bread or 263 g/day of rice represents 100% of the recommended daily intake (DRI) set at 0.6 mg/day for children aged 1–3 years. In the case of rice consumption by children of these ages, it is recommended to use bottled water for rice preparation. The consumption of the analyzed foods by teenagers and adults does not pose a health risk.